2021
DOI: 10.46303/jcsr.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Students’ Learning Progress in the Science Spiral Progression Curriculum

Abstract: The study delved into the factors the influence students’ learning progress in the implementation of the science spiral progression curriculum in selected public junior high schools in the Division of Pasig City, Philippines, covering the school year 2017 – 2018. The study used the quantitative approach to research, particularly the descriptive research methodology. The specific descriptive research designs utilized were the correlational and normative surveys. The contextual analysis technique was likewise us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…They further deposit that it enables teachers to spend more time correcting learners' misconceptions than grading learners' assessments. Further to the above, given that the current generation is technologically inclined (Zhang et al, 2019;Garcia, 2021), using ICT in administering assessments captivates and maintains learner engagement. The teachers' practices in this study were in line with this narrative.…”
Section: One Of the Quiz Questions Given By Teacher Cmentioning
confidence: 99%
“…They further deposit that it enables teachers to spend more time correcting learners' misconceptions than grading learners' assessments. Further to the above, given that the current generation is technologically inclined (Zhang et al, 2019;Garcia, 2021), using ICT in administering assessments captivates and maintains learner engagement. The teachers' practices in this study were in line with this narrative.…”
Section: One Of the Quiz Questions Given By Teacher Cmentioning
confidence: 99%
“…It is called hybrid learning and combines the characteristics of traditional schools with online learning benefits for personal delivery by providing different instructions for each group (Watson et al, 2020). This innovative concept includes the advantages of traditional and ICT-supported learning (Abass et al, 2021;Garcia, 2021;Monkeviciene et al, 2020;Ndibalema, 2021;Seage, & Türegün, 2020;Subedi & Subedi, 2020;Wahyudi, 2020;Wahyudi & Winanto, 2018). According to Carman (2002), there are five keys to applying blended learning: life events, independent learning, collaboration, assessment, performance, and supporting materials.…”
Section: The Blended Project-based Learning Modelmentioning
confidence: 99%
“…Dunton (2019) stated that the Department of Education (DepEd) in the country sees the SPA as a solution to the current education problem. However, in the context of the Philippines, many influencing factors affect students' learning ability in the science and mathematics spiral progression curriculum (Garcia, 2021). Perhaps, Orbe et al (2018) revealed that there had been a mismatch in teachers' preparation in Science and mathematics as the country implemented the SPA curriculum.…”
Section: Framework Of the Studymentioning
confidence: 99%